Souvenir Traders and Their Impact on Cultural Tourism and Economic Development - Nainggolan, Herbet; Tamba, Ojahan; Sihotang, Demita; Sinaga, Theresia (Jurnal Ilmu Pendidikan dan Humaniora, 2022)
This research delves into the dynamic role of souvenir traders in the Tomok Area of Samosir Regency, shedding light on their services and strategies and their profound impact on local tourism and the creative economy. Souvenir trading in this region transcends traditional commerce, serving as a cultural exchange that preserves Batak heritage, fuels economic growth, and contributes to the broader creative economy. The study begins by investigating the background of the research, emphasizing the cultural significance, geographical location, and economic conditions of the Tomok Area. The existing literature and related studies are reviewed, providing a comprehensive understanding of souvenir trading, tourism, and the creative economy. This background prepares the groundwork for a detailed exploration of tourism and creative economy, introducing readers to the concepts and their relevance to the Tomok Area. The research dissects the services provided by souvenir traders, highlighting their cultural engagement, authenticity, and personalization. It underlines how these services enhance the tourist experience, fostering deeper connections between visitors and the local culture. The study then uncovers the challenges faced by souvenir traders, including market competition, changing tourist preferences, and sustainability demands. A critical component of this research is the examination of successful strategies employed by souvenir traders. Real-life examples showcase how cultural engagement, product customization, collaboration with local artisans, sustainability practices, and an online presence have positively influenced their businesses and the region's economy. By acknowledging the challenges and building on their successes, traders, local authorities, and the community can collectively work toward further enriching the Tomok Area, making it a prime destination for cultural exchange and economic vitality.